Representasi Pendidikan dalam Film Indonesia Kontemporer - Sifa, Afi Layyinus; Najiullah, Rizkiyah Gustiana (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2024)
This study aims to explain the representation of education in contemporary Indonesian films and its impact on education and learning among students. The method in this study uses descriptive analysis, namely analyzing case studies of the films